Fluid management in septic patients with pulmonary hypertension, review of the literature - Asllanaj, Blerina; Benge, Elizabeth; Bae, Jieun; McWhorter, Yi (Frontiers in Cardiovascular Medicine, 2023)
The management of sepsis in patients with pulmonary hypertension (PH) is challenging due to significant conflicting goals of management and complex hemodynamics. As PH progresses, the ability of right heart to perfuse lungs at a normal central venous pressure (CVP) is impaired. Elevated pulmonary vascular pressure, due to pulmonary vasoconstriction and vascular remodeling, opposes blood flow through lungs thus limiting the ability of right ventricle (RV) to increase cardiac output (CO) and maintain adequate oxygen delivery to tissue. In sepsis without PH, avoidance of volume depletion with intravascular volume replacement, followed by vasopressor therapy if hypoperfusion persists, remains the cornerstone of therapy. Intravenous fluid (IVF) resuscitation based on individualized hemodynamic assessment can help improve the prognosis of critically ill patients. This is accomplished by optimizing CO by maintaining adequate preload, afterload and contractility. Particular challenges in patients with PH include RV failure as a result of pressure and volume overload, gas exchange abnormalities, and managing IVF and diuretic use. Suggested approaches to remedy these difficulties include early recognition of symptoms associated with pressure and volume overload, intravascular volume management strategies and serial lab monitoring to assess electrolytes and renal function.